Minimum Wages and Firm-Level Employment in a Developing Country - Fredrik Sjöholm (Research Institute of Industrial Economics (IFN), 2020)
The effect of minimum wages on employment is a matter of debate, and the existing empirical literature contains mixed results. One reason for this is the methodological difficulties involved where changes in minimum wages are endogenous to other important economic changes. To overcome this problem, we examine exogenous changes to local minimum wages in Indonesia between 1989 and 1994. Our natural experiment results from a national policy change: from minimum wages being determined by local guidelines and criteria to minimum wages being harmonized and set according to nationwide criteria. We examine how these changes in minimum wages affect employment, considering the effect both on employment within plants and on exit of plants. Our results show no evidence of an effect of minimum wages on employment in Indonesian plants. One explanation found in the data is that higher minimum wages force plants to increase productivity, which in turn enables them to retain their labor force, despite higher wage costs.
Keywords: J21; J23; J38; 330; Minimum wages; Employment; Plants; Indonesia